The Forest of Wool and Steel - Miyashita, Natsu, 1967-; Gabriel, Philip, 1953- (London : Transworld Digital, 2019)
Tomura is startled by the hypnotic sound of a piano being tuned in his school. It seeps into his soul and transports him to the forests, dark and gleaming, that surround his beloved mountain village. From that moment, he is determined to discover more. Under the tutelage of three master piano-tuners - one humble, one cheery, one ill-tempered - Tomura embarks on his training, never straying too far from a single, unfathomable question: do I have what it takes? Set in small-town Japan, this warm and mystical story is for the lucky few who have found their calling - and for the rest of us who are still searching. It shows that the road to finding one's purpose is a winding path, often filled with treacherous doubts and, for those who persevere, astonishing moments of revelation.
Translated from the Japanese.
Keywords: Piano technicians -- Fiction; Japan -- Fiction